Konseling Teman Sebaya untuk Meningkatkan Penerimaan Diri (Studi Eksperimen terhadap Santri MA TEI Multazam Bogor) - Fatimah Az-zahra Abdillah; Anisa Rahmadani; Syariful Syariful (UIN Siber Syekh Nurjati Cirebon, 2023)
This study aims to determine the effectiveness of peer counseling on santri' self-acceptance at MA TEI Multazam. There are problems regarding self-acceptance at MA TEI Multazam which are characterized by lower self-esteem, feeling inferior to friends, having difficulty opening up with others, complaining and having tendency to change physical conditions. Using the pre-experimental method, the measurement tool used is a Self-acceptance Scale (n=33) with guidelines for observation and peer counseling interventions. Peer counseling is carried out by selecting peer counselors, conducting peer counselor training with psychological first aid framework (look-listen-link), and implementing peer counseling that focused on basic counseling skill. Pre-test and post-test were carried out to measure changes in the subject's attitude before and after the intervention. The results of this study indicate that there is an increase in self-acceptance of 20.375 with sig 0.000 <0.05. The results show that peer counseling is effective in increasing santri' self-acceptance.